Dynamics of urban transformation in the practical rhetoric on the fourth meeting of AACC Comboi a la Fresca - Mateo Cecilia, Carolina; Bartual, Mijo Miquel (Re-visiones, 2024)
While it is true that the temporal proximity prevents definitive appreciations, we can confirm that in 2008 emerged an emancipatory politics on a global scale that had its turning point in 2011. This emergence involved, in the field of urban design, an intensification in the relationship between architects, sociologists, artists, and the neighbours among themselves, as well as the incorporation of collaborative and assembly practices coming from grassroots movements in urban regeneration processes, as a response to the exacerbation of the crisis of neoliberal capitalism applied to the management of the city. This article will exemplify this modus operandi within the city in the practice developed by Comboi to Fresca, the meeting held by the international network Arquitecturas Colectivas in Valencia in 2011. The starting point is how the emancipatory micropolitics that took place in Valencia did not fall into oblivion –as the product of a state of reverie– but articulated instead a dynamics of subjective urban transformation built on a foundational questioning of their own practices, and in opposition to the local modus operandi developed in Valencia.